2021
DOI: 10.1186/s40170-021-00253-w
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial metabolism as a target for acute myeloid leukemia treatment

Abstract: Acute myeloid leukemias (AML) are a group of aggressive hematologic malignancies resulting from acquired genetic mutations in hematopoietic stem cells that affect patients of all ages. Despite decades of research, standard chemotherapy still remains ineffective for some AML subtypes and is often inappropriate for older patients or those with comorbidities. Recently, a number of studies have identified unique mitochondrial alterations that lead to metabolic vulnerabilities in AML cells that may present viable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 292 publications
(263 reference statements)
2
42
0
Order By: Relevance
“…Excellent reviews reported different approaches to modify ROS levels with an anti-leukemia purpose: lowering the ROS level to prevent their role in cellular transformation or counteracting the redox adaptation by inducing oxidative stress with elevated ROS levels [ 115 , 116 ].…”
Section: The Stromal-dependent Metabolic Reprogrammingmentioning
confidence: 99%
“…Excellent reviews reported different approaches to modify ROS levels with an anti-leukemia purpose: lowering the ROS level to prevent their role in cellular transformation or counteracting the redox adaptation by inducing oxidative stress with elevated ROS levels [ 115 , 116 ].…”
Section: The Stromal-dependent Metabolic Reprogrammingmentioning
confidence: 99%
“…However, we observed an increase in both glycolysis and OXPHOS. As AML cells heavily rely on OXPHOS for cell survival and were shown to be particularly sensitive to mitochondria damaging agents [ 73 , 74 , 75 , 76 ], we observed increased sensitivity of ATG3-deficient AML cells to OXPHOS inhibiting drugs oligomycin and antimycin A whereas ATG3-depleted AML cells were resistant glycolysis inhibition ( Figure 5 C). A recent study has demonstrated that AML cell lines differ in their energy metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…This indicates that the dependency of AML cells shifts towards OXPHOS with deficient autophagy. Furthermore, targeting mitochondria is used as potential therapeutic target in combat against cancer [ 40 , 78 , 79 ] and the combination treatment of hydroxychloroquine together with mitoxantrone and etoposide (mitochondrial DNA inhibitors by topoisomerase II) is already in phase I clinical trials [ 76 ]. Besides that, Bhattacharya et al reported the potential of using SBI-0206965, an autophagy inhibitor, combined with venetoclax in AML treatment [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress-inducing effect of EANT was validated by the evidence of ROS, MitoSOX, and MMP flow cytometry in leukemia HL-60 cells ( Figure 5 , Figure 6 and Figure 7 ). Moreover, mitochondrial metabolism is a vital target for AML therapy [ 59 ]. Targeting mitochondria for ROS and MitoSOX modulations can improve the therapeutic effects of AML [ 23 , 60 ].…”
Section: Discussionmentioning
confidence: 99%